2020
DOI: 10.1007/s00464-020-07471-1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of leaks and fistulas after bariatric surgery: a systematic review and meta-analysis

Abstract: Background Endoscopic techniques have become the first-line therapy in bariatric surgery-related complications such as leaks and fistulas. We performed a systematic review and meta-analysis on the effectiveness of self-expandable stents, clipping, and tissue sealants in closing of post-bariatric surgery leak/fistula. Methods A systematic literature search of the Medline/Scopus databases was performed to identify full-text articles published up to February 2019 on the use of self-expandable stents, clipping, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
70
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 102 publications
0
70
0
6
Order By: Relevance
“…Nonoperative management with gastric stent has been used and proven effective in gastric leaks resulting from bariatric surgeries and surgical interventions of gastric cancer. In fact, it is associated with a closure rate of 92%–96% [ 4 , 7 , 8 ]. This approach was sought in our patient and showed promising results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonoperative management with gastric stent has been used and proven effective in gastric leaks resulting from bariatric surgeries and surgical interventions of gastric cancer. In fact, it is associated with a closure rate of 92%–96% [ 4 , 7 , 8 ]. This approach was sought in our patient and showed promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to reoperation, a gastric stent is a less invasive procedure, associated with decreased morbidity, mortality, and hospital stay. Additionally, stenting is advantageous because it allows patients to resume oral intake earlier [ 7 , 8 ]. However, our patient had multiple complications, including distal ulceration, migration, and para-stent leak.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of universal guidelines, there are conflicting reports on the proper care of GPF. A majority of reports agree that the laparoscopic approach and surgical interventions are definitive treatments as data indicate higher mortality with conservative management [ 7 9 ]. Meta-analysis of several case reports and retrospective studies has evaluated the outcomes of various surgical and endoscopic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of several case reports and retrospective studies has evaluated the outcomes of various surgical and endoscopic interventions. Stent placement, endoscopic clipping techniques, or surgical sealants have all shown high success rates of repair with decreased morbidity and mortality when compared to nonsurgical therapies [ 8 , 9 ]. Contemporary studies have shown improving trends with fistula repairs with evidence implying that complex endoscopic surgical treatments or combined treatment with simultaneous or sequential endoscopic methods can optimize management [ 8 ].…”
Section: Discussionmentioning
confidence: 99%